The lost symbol - Brown, Dan (Doubleday, 2009)
Called to Washington D.C., symbologist and Harvard professor Robert Langdon must investigate the centuries-old secrets of the Freemasons. However, with treachery around every corner, will Langdon's eidetic memory and insurmountable knowledge of history be able to guide him through another adventure?